ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA TURNOVER INTENTION PERAWAT DI RUMAH SAKIT SANTA ELISABETH KOTA BATAM - Sri Muharni; Utari Christya Wardhani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Turnover intention is a feeling arising from an individual, which is the intention to quit the job voluntarily according to his/her own choice. The nurse's turnover intention (ToI) tends to increase by more than 10% per year. Factors affecting turnover intention include demographic characteristics, work stress, work environment, and job satisfaction This study aims was determine the factors that influence nurse turnover intention at RSE. This research was a descriptive-analytic study using a cross-sectional study design, the sample in this study was 82 nurses. This study used a questionnaire (demographics, nurse satisfaction, nurses work stress and ToI. The results were 48.7% nurses aged 25-30 years, 84.1% female, 47.5% working period of more than 5 years, with 80. 5% nurses were not satisfied with work, and 25.6% nurses experienced work stress, nurses’ ToI 34.1% There was no correlation between job satisfaction and ToI, there was a relationship between work stress and nurse turnover intention (P value = 0.021). The conclusion of this research is the high number was influenced by external factors and by internal factors such as personal problems experienced by respondents.